Sex-Specific Association between Serum 25-Hydroxyvitamin D and Metabolic Risk Factors in T2DM Patients. (4th June 2020) - Sun, Xiaomin; Zhou, Sirui; He, Xin; Wang, Youfa; Cui, Wei
Abstract : Objective . To evaluate the relationship between serum 25-hydroxyvitamin (25(OH)D) levels and metabolic risk factor levels in patients with type 2 diabetes mellitus (T2DM) on a sex-specific basis. Methods . Our study comprised 507 patients with T2DM (321 men, 186 women; median age, 59 years). The metabolic risk factors examined included lipoprotein(a), glycated albumin (GA-L), and random blood glucose (RBG); the levels of these parameters were determined enzymatically. Serum 25(OH)D levels were measured by commercial ELISA kits. Participants were divided into low and high 25(OH)D groups according to the median 25(OH)D concentration (13.2 ng/mL). Two-way analysis of covariance and multiple linear regression analysis were performed. Results . The median 25(OH)D concentration was 13.9 ng/mL in men and 12.2 ng/mL in women. 25(OH)D levels inversely correlated with levels of three metabolic risk factors in a sex-dependent manner after adjusting for several confounding factors. These were lipoprotein(a) in men (141.3 ± 137.9 and 195.3 ± 204.8 mg/L in high and low 25(OH)D groups, respectively; P < 0.05 ); GA-L in women (22.2 ± 8.8 vs. 23.3 ± 7.3% in high and low 25(OH)D groups, respectively; P < 0.05 ). In a subgroup analysis, serum 25(OH)D levels inversely correlated with lipoprotein(a) levels in men ( β = −0.185, P = 0.002 ) and RBG levels in women ( β = −0.176, P = 0.028 ). Conclusion . Higher serum 25(OH)D levels indicate a more favorable lipid profile in men and a more favorable glucose profile in women.